2022
DOI: 10.5194/isprs-archives-xliii-b3-2022-681-2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Classifiers for Multitemporal and Multisensor Mapping of Urban Lulc Features

Abstract: Abstract. This study compares four machine-learning algorithms comprising of Classification And Regression Trees (CART), Random Forest (RF), Gradient Tree Boosting (GTB) and Support Vector Machine (SVM) for the classification of urban land-use and land-cover (LULC) features. Using multitemporal and multisensor Landsat data from 1984-2020 at 5-year intervals for the Greater Gaborone Planning Area (GGPA) in Botswana, the aim of the study is to determine the performance of the classifiers in the extraction of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…RF classifier distinguished vegetation from other classes of LULC more accurately than SVM and CART algorithms. RF and CART algorithm performance is better than SVM for built mapping of LULC because SVM underestimates the urban region ( Ouma et al 2022 ). In the present study, we observed the same trend that RF and CART classifiers had performed well in mapping the built class of the study area while SVM confused it with bare soil.…”
Section: Discussionmentioning
confidence: 99%
“…RF classifier distinguished vegetation from other classes of LULC more accurately than SVM and CART algorithms. RF and CART algorithm performance is better than SVM for built mapping of LULC because SVM underestimates the urban region ( Ouma et al 2022 ). In the present study, we observed the same trend that RF and CART classifiers had performed well in mapping the built class of the study area while SVM confused it with bare soil.…”
Section: Discussionmentioning
confidence: 99%
“…RFC minimizes the classification overfitting problem and increases the class prediction accuracy and control. As such, the RFC learning model with multiple decision trees is typically more accurate than a single decision-tree-based model, especially in detecting different LULC classes [70,71]. The overall advantage of RFC is that it can produce stable and accurate results even with minimal tuning of the hyperparameters.…”
Section: Lulc Mapping Using Machine Learning With Multiple Input Feat...mentioning
confidence: 99%
“…To evaluate the experimental results objectively, four evaluation metrics, including pixel accuracy (PA), overall classification accuracy (OA), recall (Recall), and F1 score [55,56], are selected in this paper to measure the performance of the different baseline models in the landslide recognition task to select the most suitable recognition model. PA is the proportion of the number of pixels that are true landslides among all of the pixels that were predicted to be landslides.…”
Section: Accuracy Evaluation Indexmentioning
confidence: 99%